Poetic Doors: Space for the Poetics of Unpredictability on Stage (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article examines the tool denominated poetic door as a performative device that opens space-time opportunities for the poetics of the collective unpredictability on stage. It presents how it was developed, its definition and applied examples in the productions O Amor Que Habito (2018), Uma Sonata Familiar (2018) and Luar de Contos (2019) by Coletiva Teatro. In a blocked performance, space for deviation is created with the goal of intensifying a given dramatic moment, enabling multiple new layers of meaning in real time that emerge during and as a a result of the encounter between artists and audience. The degree of poetic freedom and performativity of the device are investigated as well as the required conditions and dramaturgical implications of its use. Artist and audience become continuous reconfigurators of poetic singularities.
Keywords: Poetic door; Coletiva Teatro; Performative device; Collective creation